PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALISATION - Meizha Istiqomah; Esti Harini (Universitas Sarjanawiyata Tamansiswa, 2014)
the purpose of this research is to improve students' motivation and learning outcomes in mathematics through cooperative learning Team Assisted Individualization (TAI ) in class VIIIC SMP Kalibawang Kulon Progo . This research is Classroom Action Research (CAR) conducted in two cycles . The subjects of this study were grade students of SMP Negeri 2 Kalibawang VIIIC Kulon Progo by 23 students. Object of this study is to learn and motivation to learn mathematics. Data collection techniques in this study used observation, questionnaires, tests and documentation . The results showed that after an application using cooperative learning Team Assisted Individualization (TAI) in the class of SMP N 2 Kalibawang VIIIC Kulon Progo, motivation and learning mathematics increased student learning . This is indicated by the percentage increase in the motivation to learn an average score of 69.91 % in the pre-action , while improving on the first cycle with an average percentage of 71.77%. Increase of 77.64 % in the second cycle . The results of students' mathematics learning is also increasing. In early tests the ability of 52.71. In the first cycle, the average yield increased to 58.55. In the second cycle the average yield increased to 76.36. The results showed that motivation and learning of mathematics increases. Based on the results of the research, the math teacher can apply Team Assisted Individualization (TAI) variations in mathematical learning model.